THE APPLICATION OF ATHLETICS TOOLS IN DUE TO DEVELOP SPEED OF SECONDARY SCHOOL CHILDREN - Khanikiants, Olena; Konestyapin, Volodymyr; Rymar, Olga; Yaroshyk, Marta; Sorokolit, Nataliya (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The research is dedicated to searching of new tools for higher effectiveness of the application of athletic tools to develop speed of secondary school children. The goal of research is to prove theoretically and test experimentally the program for speed development of secondary school children (11-12 years) with priority use of athletic tools.To realize the goal such methods were applied: scientific theoretical, pedagogical observation, experiment, mathematical statistics methods. Boys are from 6 grades (11-12 years old) have participated. Pupils belong to main medical group. The results. There was elaborated and experimentally proved the program’s effectiveness. We have got statistically significant difference (p<0.05), better results from experimental group of performing control exercises: “30m run (sec)”, “30m run from place (sec)”, “run at the place during 5sec (number of movements)”. One exercise has got better result from control group - “run at the place during 5sec (number of movements)”. We have performed evaluation of students’ speed development before and after the experiment. Amount of pupils with high level of competence has grown in exercises “30m run (sec)” for 13.3%, “60m run (sec)” for 20%, “shuttle run 4×9m (sec)” for 6.7%, “long jump from place (cm) for 13.3%.